Dogs on the trail : a year in the life - Braverman, Blair; Mountain, Quince (Ecco, an imprint of HarperCollinsPublishers, 2021)
"When Blair Braverman started posting pictures of her dog team on Twitter, she had no idea the response she would get. Being a musher, after all, isn't just about racing--raising dogs from puppyhood to retirement (and beyond) is a full-time job. She and her husband, musher Quince Mountain, wanted to share stories about life with their dog team. And not just the big stuff, like expeditions and wild animal encounters, but also the everyday things: the challenge of storing a thousand pounds of raw meat, scouting new trails with the dogs, the decisions that go into putting a team together, how she trains puppies to be brave. These were goofy stories, scary stories, heartfelt stories, stories that clearly connected with people and kept going viral."--Amazon.